Intralesional Bleomycin injection in head and neck haemangioma and vascular malformation: A nonsurgical treatment - Regmi, Deepak; Bista, Meera; Shrestha, Sangita; Chhetri, Sujan Singh; Shrestha, Diva; Mahato, Nain Bahadur (Journal of Kathmandu Medical College, 2018)
Background: Successful management of vascular anomaly of head and neck region are often challenging. As the surgical modality carries high complications and bad aesthetic outcome, the treatment paradigm for these lesions has been shifting towards the non-invasive one. Because of its high sclerosing effect on vascular endothelium, low cost and easy availability intralesional Bleomycin injection can be an alternative. Objective: To determine the efficacy and safety of intralesional Bleomycin sclerotherapy for head and neck haemangioma and slow flow vascular malformation. Methods: Thirty-six patients (12 males and 24 females) with head and neck haemangioma and slow flow vascular malformations were treated with intralesional Bleomycin injection in the dose of 0.5mg/kg/dose (not exceeding 15 mg/dose) in a medical college of Nepal. The repeat injection was offered every three weeks if needed. The size of the lesion was measured and serial photographs were taken. Complications were also recorded. Results: Ten patients (28%) had complete resolution (cured), 19 patients (53%) had marked improvement five (14%) had mild improvement and two (6%) had no response. Minor complications like fever and transient rise in temperature were seen in eight patients (22%). Hyperpigmentation of the overlying skin were observed in four (11%). None of the patients developed haematological toxic side effects or pulmonary fibrosis during the follow up. Conclusion: Intralesional Bleomycin injection is simple, safe, effective and non-invasive modality of the treatment for head and neck haemangioma and slow flow vascular malformation.